Lactate based caproate production with Clostridium drakei and process control of Acetobacterium woodii via lactate dependent in situ electrolysis - Herzog, Jan; Mook, Alexander; Utesch, Tyll; Bengelsdorf, Frank R.; Zeng, An-Ping (Frontiers in Bioengineering and Biotechnology, 2023)
Syngas fermentation processes with acetogens represent a promising process for the reduction of CO2 emissions alongside bulk chemical production. However, to fully realize this potential the thermodynamic limits of acetogens need to be considered when designing a fermentation process. An adjustable supply of H2 as electron donor plays a key role in autotrophic product formation. In this study an anaerobic laboratory scale continuously stirred tank reactor was equipped with an All-in-One electrode allowing for in-situ H2 generation via electrolysis. Furthermore, this system was coupled to online lactate measurements to control the co-culture of a recombinant lactate-producing Acetobacterium woodii strain and a lactate-consuming Clostridium drakei strain to produce caproate. When C. drakei was grown in batch cultivations with lactate as substrate, 1.6 g L 1 caproate were produced. Furthermore, lactate production of the A. woodii mutant strain could manually be stopped and reinitiated by controlling the electrolysis. Applying this automated process control, lactate production of the A. woodii mutant strain could be halted to achieve a steady lactate concentration. In a co-culture experiment with the A. woodii mutant strain and the C. drakei strain, the automated process control was able to dynamically react to changing lactate concentrations and adjust H2 formation respectively. This study confirms the potential of C. drakei as medium chain fatty acid producer in a lactate-mediated, autotrophic co-cultivation with an engineered A. woodii strain. Moreover, the monitoring and control strategy presented in this study reinforces the case for autotrophically produced lactate as a transfer metabolite in defined co-cultivations for value-added chemical production.